Impact of COVID-19 on Nepalese Small and Medium Enterprises - Dangol, Jeetendra; Chitrakar, Sunil; Yoo, Kee-Seon (Journal of Business and Social Sciences Research, 2020)
This study seeks to explore the impact of COVID-19 on Nepalese SMEs. This study is based on 41 respondents from Nepalese SMEs, conducted in the first two weeks of August 2020. The questionnaires are developed in 4-point Likert scale on five major areas: current business challenges, firm’s respond to COVID-19, social response, SMEs’ perception on post COVID-19 and government’s response to COVID-19. The questionnaires are pretested for content validity and found internal consistency of instruments. The study used mean, standard deviation, and match t-test. The Nepalese SMEs give importance to social response, followed by firm’s response to COVID-19 and current business challenges. However, Nepalese SMEs are unsatisfied with the government’s response to COVID-19 and the role of government is inevitable in safeguarding SMEs.